Histostructure of the thyroid gland in the sexually mature offsprings of female rats which were exposed to passive smoking during pregnancy - Sokolova, S. S. (Journal of Education, Health and Sport, 2020)
Active smoking or passive entry of tobacco smoke into the body of a pregnant leads to the effects of nicotine on the fetus’s cells, which causes many problems of fetal development and health problems in the later life of the offspring. The researches made has conclusively proven that smoking during pregnancy contributes to the development of many endocrine disorders. The effect of tobacco smoke on the increase of leptin, C-reactive protein, decrease of adiponectin, as well as on the appearance of antibodies to islet cells of the pancreas, as the first step to the development of type 1 diabetes, was determined by epidemiological studies. In studying the effects of nicotine during lactation it was concluded that the consumption of 6 mg / kg / day of nicotine, hyperleptinemia and primary hypothyroidism develops in the newborn, and later in adulthood, all components of the metabolic syndrome. At the same time, the data on the effect of nicotine entering the mother’s body and its further influence on the offspring’s thyroid gland are few. The objective: to the study histofunctional and morphometric features of the thyroid gland of both sexes offsprings born by mothers which were exposed to "passive" smoking during pregnancy. The study object: 6-month-old Wistar rats, first-generation offspring derived from control (intact) females that were exposed to tobacco smoke components in a reproduction model of "passive" smoking. Histological and morphometric changes of the thyroid gland of 6-month-old offspring of mothers in whose bodies the products of cigarette combustion entered through the respiratory tract were studied. Morphofunctional criteria of instability and changes in the microstructure of the thyroid gland of offsprings whose mothers were exposed to nicotine in postnatal life were determined. Primary apoptotic-destructive processes in parenchyma, the formation of unstructured cell fields and microfollicles allow us to consider these offsprings as a risk group for thyroid pathology in terms of additional exposure to negative factors of "passive" smoking.